Differential DNA Methylation Encodes Proliferation and Senescence Programs in Human Adipose-Derived Mesenchymal Stem Cells - Pepin, Mark E.; Infante, Teresa; Benincasa, Giuditta; Schiano, Concetta; Miceli, Marco; Ceccarelli, Simona; Megiorni, Francesca; Anastasiadou, Eleni; Della Valle, Giovanni; Fatone, Gerardo; Faenza, Mario; Docimo, Ludovico; et al. (Frontiers in Genetics, 2020)
Adult adipose tissue-derived mesenchymal stem cells (ASCs) constitute a vital population of multipotent cells capable of differentiating into numerous end-organ phenotypes. However, scientific and translational endeavors to harness the regenerative potential of ASCs are currently limited by an incomplete understanding of the mechanisms that determine cell-lineage commitment and stemness. In the current study, we used reduced representation bisulfite sequencing (RRBS) analysis to identify epigenetic gene targets and cellular processes that are responsive to 5’-azacitidine (5’-AZA). We describe specific changes to DNA methylation of ASCs, uncovering pathways likely associated with the enhancement of their proliferative capacity. We identified 4,797 differentially-methylated regions (FDR < 0.05) associated with 3,625 genes, of which 1,584 DMRs annotated to the promoter region. Gene set enrichment of differentially-methylated promoters identified “phagocytosis,” “type 2 diabetes,” and “metabolic pathways” as disproportionately hypomethylated, whereas “adipocyte differentiation” was the most-enriched pathway among hyper-methylated gene promoters. Weighted coexpression network analysis of DMRs identified clusters associated with cellular proliferation and other developmental programs. Furthermore, the ELK4 binding site was disproportionately hyper-methylated within the promoters of genes associated with AKT signaling. Overall, this study offers numerous preliminary insights into the epigenetic landscape that influences the regenerative capacity of human ASCs.